THE EFFECT OF CHILD TOOTHPASTE CONTAINS Sodium Lauryl Sulfate (SLS) AND NOT CONTAINS Sodium Lauryl Sulfate (NON-SLS) ON PRIMARY TEETH ENAMEL SURFACE ROUGHNESS - Henri Hartman; Hartanto Endrowahyudi; Jeffrey Jeffrey; Rahmadaniah Khaerunnisa; Salsabila Auza (Fakultas Kedokteran Gigi Unjani, 2023)
Brushing teeth combined with toothpaste is influential in maintaining dental and oral hygiene, especially for children still developing. Toothpaste contains several active ingredients, including detergent in the form of Sodium Lauryl Sulfate (SLS). This study aims to determine whether or not using children's toothpaste that contains SLS and does not contain SLS on the enamel surface roughness. An experimental laboratory study was conducted on twenty primary incisors divided into two groups of treatment samples to be brushed using toothpaste containing SLS and not SLS. Toothbrushing treatment was carried out for 30 days in the morning and evening with the assumption that the accumulated time for 6 minutes was the same as the time to brush your teeth in 1 day, 2x brushing your teeth in the morning and at night. The tooth enamel surface roughness was measured before and after treatment in the middle 1/3 of the labial surface using a Mituyo SJ 301 profilometer. Statistical analysis using the Dependent t-Test showed that the P-value of the enamel surface roughness variable was less than 0.05 (P-value <0.05), thus it can be explained that there is a statistically significant mean difference between the enamel surface roughness variables before and after brushing treatment on both groups. Toothpaste that contains SLS and without SLS affects the enamel surface roughness, which can reduce the enamel surface roughness. DOI : 10.54052/jhds.v3n1.p21-30